Genome-Wide Identification and Characterization of CPR5 Genes in Gossypium Reveals Their Potential Role in Trichome Development - Wang, Heng; Umer, Muhammad Jawad; Liu, Fang; Cai, Xiaoyan; Zheng, Jie; Xu, Yanchao; Hou, Yuqing; Zhou, Zhongli (Frontiers in Genetics, 2022)
Trichomes protects plants against insects, microbes, herbivores, and abiotic damages and assists seed dispersal. The function of CPR5 genes have found to be involved in the trichome development but the researches on the underlying genetic and molecular mechanisms are extremely limited. Herein, genome wide identification and characterization of CPR5 genes was performed. In total, 26 CPR5 family members were identified in Gossypium species. Phylogenetic analysis, structural characteristics and synteny analysis of CPR5s showed the conserved evolution relationships of CPR5. The promoter analysis of CPR5 genes revealed hormone, stress, and development-related cis-elements. Gene ontology (GO) enrichment analysis showed that the CPR5 genes were largely related to biological regulation, developmental process, multicellular organismal process. Protein-protein interaction analysis predicted several trichomes development related proteins (SIM, LGO and GRL) directly interacting with CPR5 genes. Further, nine putative Gossypium-miRNAs were also identified, targeting Gossypium CPR5 genes. RNA-Seq data of G. arboreum (with trichomes) and G. herbaceum (with no trichomes) was used to perform the co-expression network analysis. GheCPR5.1 was identified as a hub gene in a co-expression network analysis. RT-qPCR of GheCPR5.1 gene in different tissues suggests that this gene has higher expressions in the petiole and might be a key candidate involved in the trichome development. Virus induced gene silencing of GheCPR5.1 (Ghe02G17590) confirms its role in the trichome development and elongation. Current results provide proofs of the possible role of CPR5 genes and provide preliminary information for further studies of GheCPR5.1 functions in trichome development.